Ethnic Preparation of Haria, a Rice-Based Fermented Beverage, in the Province of Lateritic West Bengal, India - Ghosh, Kuntal; Maity, Chiranjit; Adak, Atanu; Halder, Suman Kumar; Jana, Arijit; Das, Arpan; Parua, Saswati; Das Mohapatra, Pradeep Kumar; Pati, Bikash Ranjan; Mondal, Keshab Chandra (Ethnobotany Research and Applications, 2014)
Haria is a rice-based fermented beverage that is popular among tribal and low income people in lateritic West Bengal and East-Central India. The principal ingredient of this beverage is low grade boiled rice (Oryza sativa L.), which is mixed with a traditional starter, called bakhar, and fermented within a heat-sterilized earthen pot for 3-4 days. The main aim of this study was to investigate the ethnobotanical importance and traditional process of haria preparation. The method adopted for this study was based on interactive questionnaires and laboratory experiments. It was found that the pH decreased during the course of fermentation with increased titratable acidity of 1.42%. The alcohol content was 2-3% (v/v) in the consumable beverages. This documentation will be useful for further exploitation of haria as a health drink.